2007
DOI: 10.1370/afm.641
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression Symptoms in Primary Care and Psychiatric Care Settings: A Cross-Sectional Analysis

Abstract: For outpatients with nonpsychotic MDD, depressive symptoms and severity vary little between primary care and specialty care settings. In this large, broadly inclusive US sample, the risk factors for chronic and recurrent depressive illness were frequently present, highlighting a clear risk for treatment resistance and the need for aggressive management strategies in both settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 61 publications
(48 reference statements)
6
65
1
1
Order By: Relevance
“…These findings are consistent with those of other research in both clinical trial populations 20 and epidemiologic surveys. 21 Twenty-five to 30% of patients in our study expressed some degree of suicidal ideation according to the PHQ-9, and suicidality was correlated with severity.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with those of other research in both clinical trial populations 20 and epidemiologic surveys. 21 Twenty-five to 30% of patients in our study expressed some degree of suicidal ideation according to the PHQ-9, and suicidality was correlated with severity.…”
Section: Discussionsupporting
confidence: 92%
“…30,31 In this study, however, the clear majority of treated patients had DSM-IV diagnoses of major depressive disorder, and the mean BDI-II score indicated depression approaching the moderate range. These findings are similar to the recent larger study by Gaynes and colleagues, 32 who reported that patients with major depressive disorder in primary care settings had equivalent degrees of depression severity (moderate to severe) compared to the patients with major depressive disorder seen in psychiatric care settings.…”
Section: Resultssupporting
confidence: 89%
“…It is also possible that the self-identifiers were being prescribed antidepressants for treatment of anxiety only, but previous studies of primary care populations indicate high rates of comorbid depression and anxiety. 32 Another apparent limitation could be the method of measuring adherence, as it has been suggested that electronic medication monitoring is the gold standard of collecting data on adherence. 41 However, self-report of medi-…”
Section: Resultsmentioning
confidence: 99%
“…Due to its prominence (~20% in the general population) MDD often is referred to as the "common cold of psychiatry [2,4,5]. Worldwide, MDD causes significant economic ($83 billion in the US alone) and psychosocial burdens due to the cost of hospitalization, lost work productivity and suicide.…”
Section: The Pcp and Mdd In A Primary Care Patient Populationmentioning
confidence: 99%
“…Up to 40% of sufferers remain untreated and suicide is a common consequence; about half of suicide victims visited a PCP within the month prior to their death [2,3,7]. With the advent of multiple SSRIs many more MDD patients now are being treated and maintained in primary care practices [4,8]. Learning how to recognize MDD, therefore, is a major obstacle facing the PCP.…”
Section: The Pcp and Mdd In A Primary Care Patient Populationmentioning
confidence: 99%